Processamento Convencional de Dados Sísmicos da Bacia do Camamu - MOREIRA, Gelbson Alves (2020)
The present Course Graduate Report (TCC) has for aim the processing of seismic marine data 2-D to improve signal/noise ratio through the use of seismic techniques, to obtain seismic sections and to subsidise for more precise interpretation of subsurface structures. The treatment of seismic data is divided basically in three parts: preprocessing, processing and imaging. In the present work we discuss the steps to obtain zero o set (ZO) sections from multiple coverage using. The parts of preprocessing consisted basically of three parts: (1) organization of the geometry; (2) muting of noisy traces; and (3) ltering in the temporal frequency and velocity lter. The parts of processing consisted basically of two parts: (1) velocity analysis, (2) NMO stacking. The imaging consisted basically migration. The quality of the results is biased due to the dependence of the method on a velocity model. The sections resulting from stack and migration were interpreted aiming at the delineation of structures.